Application of semen evaluation techniques - Budai, Csilla; Egerszegi, István; Oláh, János; Jávor, András; Kovács, András (Acta Agraria Debreceniensis, 2014)
Laboratory methods of semen evaluation are used to select males for artificial insemination. The current review describes several techniques that have been recently used for sperm analysis. Conventional microscopic methods in combination with the objective computerassisted sperm motility and morphology analyzers and flow cytometry, allows to obtain more precise information about the membrane and functional status of spermatozoa. By using several methods to detect motility, viability, acrosomal and capacitation status besides DNA integrity sperm biology and some of the mechanism involved in sperm cry injury can be better understood. The number of possible targets related to sperm quality is increasing, and possible that some of them could enable sperm analysis for predicting freezability and fertility to be improved.